2005
DOI: 10.1534/genetics.105.044180
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interaction of Lobe With Its Modifiers in Dorsoventral Patterning and Growth of the Drosophila Eye

Abstract: Dorsoventral (DV) patterning is essential for growth of the Drosophila eye. Recent studies suggest that ventral is the default state of the early eye, which depends on Lobe (L) function, and that the dorsal fate is established later by the expression of the dorsal selector gene pannier (pnr). However, the mechanisms of regulatory interactions between L and dorsal genes are not well understood. For studying the mechanisms of DV patterning in the early eye disc, we performed a dominant modifier screen to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 74 publications
0
53
0
Order By: Relevance
“…We have used Drosophila eye to identify the genes required for cell survival and to sustain early growth. Previously, we have shown that ventral is the ground state of the entire early larval eye primordium (Singh and Choi, 2003), and that L/Ser are required for development of the ventral eye (Chern and Choi, 2002;Singh and Choi, 2003;Singh et al, 2005a;Singh et al, 2005b). During early eye development, little or no cell death is observed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We have used Drosophila eye to identify the genes required for cell survival and to sustain early growth. Previously, we have shown that ventral is the ground state of the entire early larval eye primordium (Singh and Choi, 2003), and that L/Ser are required for development of the ventral eye (Chern and Choi, 2002;Singh and Choi, 2003;Singh et al, 2005a;Singh et al, 2005b). During early eye development, little or no cell death is observed.…”
Section: Discussionmentioning
confidence: 98%
“…L 2 , a dominant-negative allele of L, shows loss of ventral eye in the L 2 /+ background in 100% of flies (Fig. 4A,B) (Singh and Choi, 2003;Singh et al, 2005a). We overexpressed cyclin A, cyclin B and cyclin E to accelerate cell-cycle progression in the L 2 /+-mutant background and did not find any significant rescues (data not shown).…”
Section: Loss Of L/ser Causes Induction Of Cell Death In the Eye Imagmentioning
confidence: 88%
See 1 more Smart Citation
“…Total chlorophyll content was estimated by the method of Lichtenhaler, 15 total protein released was analysed by Lowry et al, 16 elemental analysis P, Mg, Fe, Cu was done as described by Jackson. 17 Plant P was estimated as described by Singh et al 18 The Fungi was isolated following the standard procedure. 19 Nitrate reductase activities was estimated following Jawarski, 20 while Aryl sulfatase and Esterase was estimated by Tabatabai and Bremner 21 and Schnurer and Rossawall, 22 respectively.…”
Section: Greenhouse Experimentsmentioning
confidence: 99%
“…L mutants have reduced adult eyes and exhibit ectopic apoptosis during eye development, indicating that L is required for eye development (Chern and Choi, 2002;Singh et al, 2005;Singh et al, 2006). But whether it regulates eye development via regulation of TORC1 activity is unknown.…”
Section: Introductionmentioning
confidence: 99%